Implementation of Islamic Service Excellence in Savings Pick Up Service in Baitul Mal Wa Tamwil - Miratul Khoiriyah; Lely Ana Ferawati Ekaningsih (SAINTIS Publishing, 2025)
The implementation of Islamic Service Excellence (ISE) in savings pick-up services in Baitul Mal wa tam wil (BMT) is very important to improve service quality and customer satisfaction. This service allows customers to make deposits without having to visit the office, providing better accessibility. BMT prioritizes sharia principles, including the A6 principle: Accountability, Trust, Fairness, Adaptive, and Affirmation. This article discusses the main components of implementing Islamic Servic Excellence, such as employee training, technology utilization, personal approach, and customer engagement. Through this strategy, BMT focuses on operational efficiency and building strong relationships with customers. The implementation of Islamic service excellent (ISE) is expected to create a superior service experience, strengthen trust, and improve BMT's reputation as a professional Islamic financial institution. This study emphasizes the importance of integrating sharia values in savings pick-up services to support community economic growth.